2021
DOI: 10.26803/ijlter.20.7.13
|View full text |Cite
|
Sign up to set email alerts
|

Examining Mathematical Problem-Solving Beliefs among Rwandan Secondary School Teachers

Abstract: This study explored teachers' beliefs about mathematical problem-solving. It involved 36 identified teachers of Kayonza District in Rwanda via an explanatory mixed-method approach. The findings indicate that most teachers show a positive attitude towards advancing problem-solving in the mathematics classroom. However, they expose different views on its implementation. Role of problem-solving, Mathematical problems, and Problem-solving in Mathematics were identified as main themes. Problem-solving was highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
0
13
0
1
Order By: Relevance
“…They found that successful completion of in-service training has a positive and far-reaching impact on professional competence as it improves science curricula implementation and raises science 'teachers' attitudes towards the teaching profession. In the same line, Dorimana et al (2021) found out that most participants, after attending the training, acknowledged having acquired knowledge such as simulation with the PBL process, researching learning topics, and active discussion of how research materials are applied to solve problems. This knowledge acquisition significantly changed 'teachers' initial negative perceptions of PBL and motivated them to apply its principles in real-life scenarios (Zaidi et al, 2010).…”
Section: Discussion Of Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…They found that successful completion of in-service training has a positive and far-reaching impact on professional competence as it improves science curricula implementation and raises science 'teachers' attitudes towards the teaching profession. In the same line, Dorimana et al (2021) found out that most participants, after attending the training, acknowledged having acquired knowledge such as simulation with the PBL process, researching learning topics, and active discussion of how research materials are applied to solve problems. This knowledge acquisition significantly changed 'teachers' initial negative perceptions of PBL and motivated them to apply its principles in real-life scenarios (Zaidi et al, 2010).…”
Section: Discussion Of Resultsmentioning
confidence: 96%
“…They do not only need instruction but also access to the world to relate the knowledge already possessed with that in the real-world setting (Sterling, 2013). The effectiveness of the use of PBL depends on several factors, including the knowledge teachers have about the whole teaching and learning process (Dorimana et al, 2021).…”
Section: Concept Of Problem-based Learning (Pbl)mentioning
confidence: 99%
See 1 more Smart Citation
“…The current data got a reliability coefficient of .73 Cronbach alpha of internal consistency. The analysis of VASS is done by counting the number of students who selected a certain scale or computing the average of the scale along with each respondent (student) [12] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…In fact, there was a need to shift from teacher-centered to learner-centered because it has been proved that learners learn well when they are given the opportunity to learn with their peers instead of sitting passively in their class and listening to the teacher. To achieve this, active learning techniques such as the cooperative learning approach ( Sibomana et al., 2021 ), game-based approach ( North et al., 2021 ), problem-solving approach ( Dorimana et al., 2021 ), and others should be brought to the classroom.…”
Section: Introductionmentioning
confidence: 99%